Vietnam : Business opportunities and risks, a guide to success in Asia's next dragon - Quinlan, Joseph P. (Heinemann Asia, 1995)
Contents: Ten things business should know about Vietnam; the polotical landscape; Vietnam: an economic overview; major economic sectors: overview and outlook; the fundamentals of foreign trade; the operating environment; key operating rules of foreign...